APPLICATION OF BLOWER DOOR MEASUREMENTS IN THE EVALUATION OF WORKMANSHIP INFLUENCE IN AIRTIGHTNESS - Nuno Ramos (2013)
A large social housing retrofitting program was implemented in Porto, Portugal, a mild climate region. One of the features of that program was the upgrade of windows and ventilation systems. An increased airtightness was expected and mechanical extraction on kitchens and bathrooms was implemented. This work analyses the changes in building airtightness that resulted from that renovation. A large sample of identical dwellings was analysed using the blower door test. This analysis was performed in a set of dwellings that were identical and also identically renovated. As two different contractors were involved in the renovation of specific sub sets of those dwellings, the opportunity to use the blower door test as an indicator of workmanship quality was created. The results of this work therefore include not only the airtightness of the renovated buildings but also the variability of ACH50 values for each subset of dwellings, allowing for conclusions on the workmanship effect. The analysis of the adequacy of the resulting airtightness is also performed, regarding the specific climate conditions and the typical user behaviour of the dwellings. Finally, the user modifications also proved to be of high importance to the found airtightness.